(untitled) (Journal of the College of Basic Education, 2026)
The current research aims to investigate the effect of the (5Ws&1H) strategy on the achievement of second-year intermediate students in physics. The researchers purposively selected the Bashiqa Intermediate School for Boys, affiliated with the Nineveh Directorate of Education. They also selected section (B) with (24 students) to represent the experimental group and section (A) with (22 students) to represent the control group. The researchers conducted equivalence procedures between the students of the two research groups in a number of variables that could potentially influence the study results, namely (prior knowledge test, prior achievement in physics, and Raven’s Inventory). The curriculum to be taught during the experiment was determined to consist of three chapters from the second-year intermediate physics textbook. Behavioral objectives for the prescribed topics were formulated, totaling (74) behavioral objectives distributed according to Bloom’s Taxonomy of Cognitive Levels (knowledge, comprehension, application, and analysis). To achieve the research objectives, the researchers developed a research instrument consisting of an achievement test The test consisted of (30) objective multiple-choice questions with four alternatives each. Face validity was verified by presenting the test to a panel of experts. Content validity was established based on the extent to which the test items matched the content of the taught curriculum, as well as the difficulty index, discrimination index, and the effectiveness of the incorrect alternatives for each item, using appropriate statistical methods. Test reliability was established using the Kopder-Richardson-20 formula and the SPSS statistical software package. After statistical analysis, it was found that second-year intermediate students who received instruction using the (5Ws&1H) strategy showed a tangible positive impact on raising the achievement level of the experimental group compared to the achievement level of the control group, who were taught using the traditional method.